ANALISIS KESTABILAN MODEL LESLIE-GOWER DENGAN PENGARUH WAKTU TUNDA DAN PEMANENAN PROPORSIONAL - Azhari Kemalasari; Rina Reorita; Renny Renny (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
The main purpose of this research is to study the Leslie-Gower model and the response of the Holling type II with time delay and proportional harvesting. The method used in the completion of the model is qualitative, namely by analyzing the stability of the model's equilibrium point. The Leslie-Gower model and Holling type II response with delay time and proportional harvesting have four equilibrium points. There is one point of unstable equilibrium and one point of equilibrium that is stable. Meanwhile, for the other two equilibrium points, it depends on the value of the parameters taken. The delay time resulted in oscillations in the model. The greater the delay time value used, the greater the inequality in oscillations that occur in the system. This means the model will take longer to stabilize.